Pengembangan E-Modul Berbasis Etnomatematika Berkonteks Pertanian Padi pada Pembelajaran Materi Perbandingan Kelas VII - Yasin Fajar Augusta; Rasiman; Sudargo (Pascasarjana Universitas PGRI Semarang, 2025)
The aim of this research is to describe the validity, practicality and effectiveness of comparative e-modules in the context of ethnomathematics-based rice farming. This research uses the RND (Research and Development) research method with the ADDIE development model. In this development model there are 5 stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data collection in this research used questionnaires and tests. The research instruments include media expert validation questionnaires, material expert validation questionnaires, student practicality questionnaires, expert evaluation questionnaires and post test questions. The data analysis technique in this research uses experimental design analysis. The media expert validator result on the validation sheet was 0.8708 with very good criteria, the material expert validator result was 0.960938, while the evaluation expert validator result on the validation sheet was 0.9166667 with very high criteria. The results of the questionnaire measuring student practicality were 88.6% in the very good category. The trial results show the difference between classes that use comparative material e-modules in the context of rice farming, based on ethnomathematics, the effectiveness value is 1.9114, meaning that learning uses comparative material e-modules in the context of rice farming, based on ethnomathematics.